2016
DOI: 10.1371/journal.pone.0153374
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Uptake Mediated by Trk1 Is Crucial for Candida glabrata Growth and Fitness

Abstract: The maintenance of potassium homeostasis is crucial for all types of cells, including Candida glabrata. Three types of plasma-membrane systems mediating potassium influx with different transport mechanisms have been described in yeasts: the Trk1 uniporter, the Hak cation-proton symporter and the Acu ATPase. The C. glabrata genome contains only one gene encoding putative system for potassium uptake, the Trk1 uniporter. Therefore, its importance in maintaining adequate levels of intracellular potassium appears t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 55 publications
(80 reference statements)
1
15
0
Order By: Relevance
“…To confirm the predicted potassium uptake function of both putative C. krusei Trk transporters, we cloned the corresponding ORFs into two S. cerevisiae multicopy vectors behind the NHA1 promoter and tagged their 3′ termini with the GFP sequence in one of the two plasmid series (Table ). The weak and constitutive promoter of the NHA1 gene, which encodes a potassium and sodium efflux system (the Nha1 antiporter), has been already repeatedly successfully used for the expression of heterologous Trk transporters in S. cerevisiae (e.g., TRK1 genes from Z. rouxii or C. glabrata ; Llopis‐Torregrosa, Husekova, & Sychrova, ; Stribny et al, ; Zimmermannova, Salazar, Sychrova, & Ramos, ).…”
Section: Resultsmentioning
confidence: 99%
“…To confirm the predicted potassium uptake function of both putative C. krusei Trk transporters, we cloned the corresponding ORFs into two S. cerevisiae multicopy vectors behind the NHA1 promoter and tagged their 3′ termini with the GFP sequence in one of the two plasmid series (Table ). The weak and constitutive promoter of the NHA1 gene, which encodes a potassium and sodium efflux system (the Nha1 antiporter), has been already repeatedly successfully used for the expression of heterologous Trk transporters in S. cerevisiae (e.g., TRK1 genes from Z. rouxii or C. glabrata ; Llopis‐Torregrosa, Husekova, & Sychrova, ; Stribny et al, ; Zimmermannova, Salazar, Sychrova, & Ramos, ).…”
Section: Resultsmentioning
confidence: 99%
“…We first amplified CaSAT1 from YEp352‐SAT1, resulting in several specific PCR fragments (data not shown). Llopis‐Torregrosa et al () suggested that regulatory elements upstream and downstream sat1 gene were not necessary to confer ClonNAT resistance. Thus, the chimeric primer pairs were designed to include ACT1 exon 1, the subsequent intron, and the full‐length sat1 ORF (Table and Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…In absence of a Z. rouxii ‐tailored CRISPR‐Cas9 system, Cre‐ loxP system is preferable over hisG and lacZ systems as marker recycling method as it may be applied in prototrophic strains and avoids a counterselection such as growth on media supplemented with 5‐fluoroorotic acid (5‐FOA) for URA3 excision (Steensma & Ter Linde, ). To construct a Z. rouxii plasmid containing cre gene and ClonNAT R as dominant marker, we cloned cre gene under the control of the inducible pScGAL1 promoter (pScGAL1 + cre) into pCg2XpH‐N (Llopis‐Torregrosa et al, ) by HR in S. cerevisiae (Figure a). First, the pScGAL1 + cre construct was PCR‐amplified from pZCRE donor plasmid (Pribylova, De Montigny, et al, ) with the chimeric primers CRE‐pGRB‐SacI‐XbaI‐F1 and CRE‐pGRB‐XhoI‐XbaI‐R1 (Figure b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations